Adverse Events in Patients With Rheumatoid Arthritis and Psoriatic Arthritis Receiving Long-Term Biological Agents in a Real-Life Setting - de Camargo, Mayara Costa; Barros, Bruna Cipriano Almeida; Fulone, Izabela; Silva, Marcus Tolentino; Silveira, Miriam Sanches do Nascimento; Camargo, Iara Alves de; Barberato-Filho, Silvio; Del Fiol, Fernando de Sá; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2019)
Background: Biological agents used for the treatment of psoriatic arthritis (PsA) and rheumatoid arthritis (RA) are associated with serious adverse effects (SAEs). Although several biologics have demonstrated good efficacy and tolerability in short-term trials, treatment guidelines recommend them as third line therapies due to a relative lack of long-term safety data. Objective: To determine the frequency and severity of adverse effects associated with the long-term use of biologics in the treatment of PsA and RA, and possible risk factors for such events in a real-life setting. Methods: We conducted a longitudinal study in PsA and RA patients only taking long-term biological agents from 2003 to 2011. Sources of information included dispensing pharmacy data and interviews with patients. Research staff conducted telephone interviews with patients inquiring about any apparent medication-related adverse drug reactions (ADRs) or SAEs. ADR/SAE’s data was based on pharmacy reports. We conducted a multivariate analysis to identify the factors associated with the risk of ADRs. Results: Of the 305 patients identified, we interviewed 268 patients. Most of these were taking adalimumab 127 (47.4%), 52 (19.4%) etanercept, 42 (15.7%) infliximab, 25 (9.3%) rituximab, 10 (3.7%) abatacept, 9 (3.4%) efalizumab, and 3 (1.1%) tocilizumab. Of the 268 patients, 116 (43.3%) experienced one or more adverse events related to biological agents with 1.6 events per patient, and of these 29 (25%) experienced one or more SAEs, with majority subjected to hospitalizations. The most frequently reported ADRs were administration site reactions as observed in 73 patients (27.2%), infections in 30 patients (11.2%), effects on nervous system in 22 patients (8.2%), and 15 (5.6%) patients withdrew due to ADRs. The use of rituximab was related with less risk of ADR [PR 0.42, 95% CI 0.18-0.96; p = 0.04] than other agents. The monitoring of patients (medical consultation and laboratory test) was only completed by 48 patients (30.4%). Conclusion: the data showed the early of the biologic agents experience in Brazil, which were associated with ADRs, withdrawals due to ADRs and SAEs. The quantification of adverse effects (serious or nonserious) considering close monitoring and patients’ perceptions are increasingly important for future decision-making.